2005
DOI: 10.1007/s10508-005-1001-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Rape on Men: A Descriptive Analysis

Abstract: Previous studies of the effects of rape on men have focused mainly on clinical populations. This study extended current research by investigating the effects of rape on a non-clinical sample of men recruited from the general population by media advertising. A total of 40 male rape victims were asked to provide details of their assaults, levels of psychological disturbance, long-term effects, and reporting issues. Results revealed that most assaults had been carried out using physical or violent force, in a var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
261
10
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(305 citation statements)
references
References 29 publications
22
261
10
3
Order By: Relevance
“…On the other hand, some studies suggest that men tend to deny the impact of sexual abuse on their lives in order to cope. Furthermore, men rape victims assume they will experience negative treatment, be disbelieved, or be blamed for their assault, all of which pose barriers to seeking help for their assault (Walker et al, 2005). This study also showed that childhood rape victims were less likely to seek professional help.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…On the other hand, some studies suggest that men tend to deny the impact of sexual abuse on their lives in order to cope. Furthermore, men rape victims assume they will experience negative treatment, be disbelieved, or be blamed for their assault, all of which pose barriers to seeking help for their assault (Walker et al, 2005). This study also showed that childhood rape victims were less likely to seek professional help.…”
Section: Discussionmentioning
confidence: 61%
“…This study identified that factors associated with an increased likelihood of professional help seeking include being threatened during the incident, physical injury as a result of the incident, and sexual assault perpetrated by family or friend. A study conducted by Walker et al (2005) suggested that men might be more likely to report a rape to medical services only if they are severely physically assaulted. Men victims perpetrated by family or friends were more likely to seek professional help.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may be particularly relevant for victims of crimes which are known to elicit high levels of victim-blame (e.g., sexual assault against heterosexual and LGBT victims, domestic violence) (e.g., Davies and Rogers, 2006;Davies and Hudson, 2011). Victim concerns about, and experiences of, perceived judgements or blame by others can lead to the experience of secondary victimisation which can further reinforce associated trauma symptomology (e.g., Walker, Archer and Davies, 2005;Lowe et al, 2015). This represents an additional barrier to engagement with support services as victims may be anxious about how they might be perceived or judged by practitioners (Lowe et al, 2015).…”
mentioning
confidence: 99%